New arrangements for forest science (discussion paper prepared for the intergovernmental panel on forests, fourth session, New York, Feb 97 (1997)
As forest scientists widen their field of view and look at problems in a across-sectoral way, and with a sense of history, they start to ask, and aswer, more of the pressing questions. If they adopt an analytical, rather than a descriptive approach, they will make many new discoveries. The new policy environment in which forest science now has to operate reflects a growing concern about environmental change, locally and globally, and the need to control this through more sustainable development. The heart of the problem is to achieve a balance between the needs of all people; to recognise that changes in forest health have multiple impacts on both local and global environments. Forests are a key part of the interface between humanity and the environment. They can no longer be studied as though they are simply "outdoor factories to produce wood-fibre", divorced from society and as if forest activities are only of local concern. In the real world, forests play a fundamental role in society and can have impacts at all scales. As more forest scientists, and others, appreciate this, the world will realise the true importance of forests and their central role in sustainable development. Collectively, IUFRO, FAO and CIFOR present an (exciting) opportunity to ensure clients' priorities for forest research are properly identified, and to respond accordingly.